Pendampingan inovasi bahan ajar kreatif dan menyenangkan dengan pemanfatan Media Canva di SDN Lesanpuro 3 - Kusuma, Adi Candra; Putra, Dimas Rossiawan Hendra; Ekasari, Silvia Rahmi; Hairus, Hairus; Dewatama, Denda; Fauziyah, Mila (Penamas: Journal of Community Service, 2025)
Engaging and interactive learning media are crucial in enhancing students’ understanding of the material presented by the teacher. Learning at SDN Lesanpuro 3 still employs a teacher-centered approach characterized by limited student interaction and minimal use of media. Community service activities aim to enhance teachers’ skills in creating innovative teaching materials by utilizing Canva media to foster a pleasant learning atmosphere. The training participants were 14 teachers from SDN Lesanpuro 3 Malang, who underwent training using the Participatory Action Research (PAR) method. This method was technically carried out through seminars (theory-based), demonstrations, and direct practice, where the role of lecturers and students facilitated teacher empowerment. The results of community service activities (PPM) enhance teachers’ understanding of creating innovative teaching materials by utilizing Canva media effectively. This community service activity enhanced teachers’ abilities in using Canva for designing interactive teaching materials. Evaluation before and after the training showed a positive response, with 85.7% of teachers demonstrating improved ability to create interactive content.